TRIM22 genotype is not associated with markers of disease progression in children with HIV-1 infection - Boswell, Michael T (AIDS, 2021)
OBJECTIVE: Untreated perinatal HIV-1 infection is often associated with rapid disease progression in children with HIV (CWH), characterised by a high viral loads and early mortality. TRIM22 is a host restriction factor which directly inhibits HIV-1 transcription, and with genotype variation reported as associated disease progression in adults. We tested the hypothesis that TRIM22 genotype is associated with disease progression in CWH. DESIGN: ART-naïve CWH, aged 6 to 16 years, were recruited from primary care clinics in Harare, Zimbabwe. We performed a candidate gene association study of TRIM22 genotype and haplotypes with markers of disease progression and indicators of advanced disease. METHODS: TRIM22 exons three and four were sequenced by Sanger sequencing and single nucleotide polymorphisms were associated with markers of disease progression (CD4+ T cell count and viral load) and clinical indicators of advanced HIV disease (presence of stunting and chronic diarrhoea). Associations were tested using multivariate linear and logistic regression models. RESULTS: A total of 241 children, median age 11.4 years, 49% female, were included. Stunting was present in 16% of participants. Five SNPs were analysed including rs7935564, rs2291842, rs78484876, rs1063303 and rs61735273. The median CD4+ count was 342 (IQR: 195 - 533) cells/μL and median HIV-1 viral load 34 199 (IQR: 8211 – 90 662) IU/mL. TRIM22 genotype and haplotypes were not associated with CD4+ T cell count, HIV-1 viral load, stunting or chronic diarrhoea. CONCLUSION: TRIM22 genotype was not associated with markers of HIV disease progression markers or advanced disease in CWH.